A label-free G-quadruplex aptamer fluorescent aptasensor for visual and real-time kanamycin detection in lake and human samples. Issue 2 (9th December 2022) - Ma, Yingnan; Shen, Gang; Li, Runzhi; Wang, Changzheng; Yang, Fengmin; Wang, Fangfang; Ye, Huanfeng; Zhang, Hong; Tang, Yalin
Abstract : A label-free, visual and real-time fluorescent aptasensor based on H-aggregate disassembly of a chiral cyanine dye induced by the G-quadruplex aptamer for kanamycin detection. Abstract : Antibiotic abuse is considered a serious problem affecting human health, necessitating that great attention be paid to explore robust, simple and sensitive methods for rapid evaluation. In this paper, we developed a fluorescent aptasensor for visual and real-time kanamycin detection by taking advantage of the label-free strategy based on H-aggregate disassembly of a chiral cyanine dye induced by a G-quadruplex aptamer. The good sensitivity and selectivity enabled this aptasensor to have a detection limit as low as 43 nM and have high specificity for kanamycin recognition. Furthermore, this assay was successfully applied for the detection of kanamycin in lake water and urine with excellent recoveries.